2022
DOI: 10.3390/horticulturae8070593
|View full text |Cite
|
Sign up to set email alerts
|

Possibility of Vegetable Soybean Cultivation in North Europe

Abstract: The interest in cultivation of vegetable soybeans, also known as edamame, in the North Europe region has increased during the last years due to their high nutritional value and excellent taste properties. During the last decade the possible growing area for soybeans has expanded towards the north due to changes in climate as well as breeding efforts. In order to adopt vegetable soybean growing technology for commercial cultivation in the North Europe region, independent experiments were carried out in Latvia a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 25 publications
0
6
0
Order By: Relevance
“…Cultivation of legumes is of great importance for the application of crop rotation and is an important element of biodiversity. With the progression of climate warming, many scientists and crop experts from a variety of offices began to test soybean varieties in northern latitudes [3,12,24,25,37]. However, in order to be successful in cultivation in northern latitudes, one needs to grow stable varieties of the proper vegetation length [3].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Cultivation of legumes is of great importance for the application of crop rotation and is an important element of biodiversity. With the progression of climate warming, many scientists and crop experts from a variety of offices began to test soybean varieties in northern latitudes [3,12,24,25,37]. However, in order to be successful in cultivation in northern latitudes, one needs to grow stable varieties of the proper vegetation length [3].…”
Section: Discussionmentioning
confidence: 99%
“…Soybean is a short-day plant, which is especially susceptible to the latitude of the growing site [2,3]. It's suitability to the region is restricted by long daytime duration, low temperature at the time of germination and flowering, and amount of rainfall [4].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Canada continues to export food grade soybeans, including vegetable soybeans to the Asian market ( (accessed on 1 February 2022)). A study conducted in Latvia and Norway [ 39 ] showed the potential for successful cultivation of vegetable soybeans at higher latitudes, such as the Nordic–Baltic region in North Europe, with yield levels comparable to other regions of the world.…”
Section: Global Area Production and Productivitymentioning
confidence: 99%